Taxonomy and diversity of coelobite bryozoans from drift coral cobbles on Co To Island, northern Vietnam - Dick, Matthew H.; Ngai, Nguyen Danh; Doan, Hung Dinh (Zootaxa, 2020)
There has been no previous report detailing the taxonomy of marine bryozoans along the coasts of Vietnam. Here we report on the taxonomy and diversity of bryozoans collected among drift coral cobbles from a beach in the tropical Co To archipelago, Gulf of Tonkin, northern Vietnam. We detected 27 bryozoan species (23 cheilostomes, four cyclostomes) in a coelobite assemblage inhabiting crevices in the cobbles, and holes made by boring molluscs. The degree of bryozoan preservation varied greatly, suggesting that the cobbles had accumulated on the beach over a period of months to years, or even decades. Coral reefs in the Co To archipelago underwent a catastrophic decline in 2003–2008, and it is unclear whether the bryozoan assemblage reflects past diversity, present diversity remaining in the coral rubble, or both. We describe six new species: Parasmittina acondylata n. sp., Metroperiella cotoensis n. sp., Microporella tonkinensis n. sp., Rhynchozoon setiavicularium n. sp., R. latiavicularium n. sp., and Disporella phaohoa n. sp. All but two of the previously described species were already known from the Central Indo-Pacific coastal biogeographical realm of Spalding et al. (2007), which includes Vietnam. We report the third Recent record of the thalamoporellid Dibunostoma reversum (Harmer, 1926), which is quite similar to and might be conspecific with the lower Miocene species Thalamoporella transversa Guha & Krishna, 2004; while it is premature to synonymize the two, we transfer T. transversa to Dibunostoma, as D. transversum. The calcareous, sheet-like, encrusting foraminiferan Planorbulina larvata was prominent in the coelobite assemblage and was often observed in substrate competition with bryozoans. A limited analysis of competitive interactions indicated that the encrusting bryozoans in the coelobite assemblage encountered P. larvata more often than they encountered other bryozoans, and that P. larvata out-competed bryozoans for substrate, reinforcing a growing sense of the importance of encrusting foraminifera in tropical and subtropical hard-substrate communities.